2020
DOI: 10.3390/w12051411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consecutive Extreme Weather Events on a Temperate Dystrophic Lake: A Detailed Insight into Physical, Chemical and Biological Responses

Abstract: Between May and July 2018, Ireland experienced an exceptional heat wave, which broke long-term temperature and drought records. These calm, stable conditions were abruptly interrupted by a second extreme weather event, Atlantic Storm Hector, in late June. Using high-frequency monitoring data, coupled with fortnightly biological sampling, we show that the storm directly affected the stratification pattern of Lough Feeagh, resulting in an intense mixing event. The lake restabilised quickly after the storm as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 102 publications
2
19
0
Order By: Relevance
“…Previously, Shade et al (2010) [16] found a significant relationship between the Schmidt stability of a lake in Taiwan and the differences in bacterial communities in the epilimnion and hypolimnion. Calderó et al (2020) [58] saw a decrease in the biovolume of Cyanobacteria and an increase in diatoms in Lough Feeagh on May 28 in the same study year. Both the high stability and the changes in phytoplankton biomass presumably have also influenced the shift in the free-living bacterial community.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Previously, Shade et al (2010) [16] found a significant relationship between the Schmidt stability of a lake in Taiwan and the differences in bacterial communities in the epilimnion and hypolimnion. Calderó et al (2020) [58] saw a decrease in the biovolume of Cyanobacteria and an increase in diatoms in Lough Feeagh on May 28 in the same study year. Both the high stability and the changes in phytoplankton biomass presumably have also influenced the shift in the free-living bacterial community.…”
Section: Discussionmentioning
confidence: 82%
“…The availability of DO was associated with samples taken in the spring, when DO was highest and the lake was fully mixed and slowly began to stratify [58]. High values for Chl a and Schmidt stability defined the bacterial community in the summer, when the lake was unusually stable and phytoplankton biomass reached a relatively high peak [58]. Color was correlated with the samples taken in the autumn.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations